Assessment of Healing Forest Potential for Nature-Based Tourism in Bogor Botanical Gardens - Riswan, Arbi Pangestu; Hasibuan, Ratna; Sasongko, Dwi Agus (Talenta Publisher, 2026)
Healing forest activities, such as Bogor Botanical Gardens, have become increasingly popular among urban communities, especially those experiencing stress or seeking peace. Healing forests offer a calming effect on the body, soothe the mind, and create a sense of comfort that can help lower stress levels through relaxation activities immersed in nature (natural healing). This study aimed to identify potential areas suitable for forest-healing activities based on the standards outlined in the SNI 9006:2021. This study uses a mixed-method approach combined with field observations. The collected data were analyzed using a descriptive method. The results showed that one location, Area Six, has a strong potential for Healing Forest activities. Based on on-site analysis, activities that can be carried out in this area include yoga, forest walks, tree-hugging, and simply enjoying natural surroundings.